2008
DOI: 10.1007/s11845-008-0261-9
|View full text |Cite
|
Sign up to set email alerts
|

Irish coroners’ attitudes towards suicide and its prevention

Abstract: Irish coroners favour communication about suicide and have a positive attitude towards its prevention but they appear to underestimate the prevalence of mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Prior research found that approximately one in five subjects reported a favourable attitude towards suicide as a means to end one's life, in particular when they were confronted with a severe incurable disease (Farrow et al 2009;Wright 2012). Research suggests differences between men and women's attitudes toward suicide regarding: ''permissiveness factor'' for example, in the case of an individual with an incurable disease (Dahlen and Canetto 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research found that approximately one in five subjects reported a favourable attitude towards suicide as a means to end one's life, in particular when they were confronted with a severe incurable disease (Farrow et al 2009;Wright 2012). Research suggests differences between men and women's attitudes toward suicide regarding: ''permissiveness factor'' for example, in the case of an individual with an incurable disease (Dahlen and Canetto 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Impetus for the decrease in autopsy rates may have emanated from changing attitudes among physicians, medical students, and relatives of suicide victims toward autopsies, which in turn could have affected the allocation of funding. 20,21,[43][44][45][46][47][48][49] At a higher level of abstraction, an ever-increasing demand for costeffectiveness in the health system may have decreased autopsy rates and diverted available funds to other priorities, such as improvement of mental health services. Hence, decreasing suicide rates may be a joint product of artifactual factors that increase misclassification and substantive factors that improve mental health treatment.…”
Section: Implications For Vital Statistics and Epidemiologymentioning
confidence: 99%
“…Moreover, reliable and valid suicide data may be rarely available in developing countries. In countries with coronial systems, research has shown that coroners may differ in findings of suicide, the interpretation of evidence, and the interpretation and application of coronial law relating to suicide determination in practice [4,6,7]. Undercounting or misclassification of suicide is of great concern within the academic and public health sphere [8,9].…”
Section: Introductionmentioning
confidence: 99%